DAMPAK DAN FUNGSI SOSIAL MITOS MBAH BAJING BAGI KEHIDUPAN SPIRITUAL MASYARAKAT DUSUN KECOPOKAN, KABUPATEN MALANG, JAWA TIMUR - Eggy Fajar Andalas (Universitas Andalas, 2017)
This study aims to describe the social impact and function of the Myth of Mbah Bajing towards its readers (Kecopokan village’s people). This research is a descriptive-qualitative with the Sociology of Literature approach. The data sources of this study are the observation, the interview and the questionnaire to the informants that show the social impact and function of the myth towards Kecopokan village’s people. The procedures of data collection are done by some techniques which are 1) recording, 2) photography, 3) observation, 4) quotation, 5) interview, 6) distributing the questionnaires. The results of this study show that the social impact of the Myth of Mbah Bajing in Kecopokan village social life is reflected through the way people think, act, and behave towards Mbah Bajing’s spirit and grave. Furthermore, there is a special treatment to this mythological figure as the part of the spiritual life of Kecopokan village’s people. This myth has also the social functions towards Kecopokan village’s people as 1) the education instrument especially for young generation, 2) the strengthener of the solidarity among the people and 3) the norms regulator in their social life. Keyword: function, impact, myth, sociology of literature